Introduction: Primate relatives - Anna Albiach-Serrano (Mètode Science Studies Journal: Annual Review)
The order Primates includes more than three hundred species, among which are us, human beings. Perhaps that is why we are so fascinated by their study, because of the diverse forms and behaviours of the taxon and because to understand primates better is to understand ourselves better.